The Effectiveness of STEM-Based PjBL on Student’s Critical Thinking Skills and Collaborative Attitude - Bulu, Vera Rosalina; Tanggur, Femberianus (Universitas Islam Raden Intan Lampung, INDONESIA, 2021)
PjBL and STEM learning models can overcome the lack of critical thinking skills and collaboration. Those learning models involve 4C that support students’ critical thinking skills and collaboration. This study aimed to identify the effectiveness of STEM-based PJBL models on students’ critical thinking skills and collaborative attitudes. This study was quantitative research with a descriptive method. The data had been collected using a critical thinking skills test, collaborative attitude questionnaires, and learning observation guidelines. Before performing data analysis, the researchers performed prerequisite tests consisting of the normality test, homogeneity test, variance-covariance matrix homogeneity test, N-Gain test, and effectiveness test. The basic assumption test results showed that the MANOVA test could be performed. The MANOVA test results revealed that the STEM-based PjBL learning model effectively improved students' critical thinking skills and collaborative attitudes.